The Effects of Climate Change on the Existing Environmental Laws and the Impact on Natural Resources - Kalala, Sapard Vincent-de Paul Mozes Mulumba Ngandu Tshimankinda (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
Sustainable development is meeting the need of the present societal setting without jeopardizing the stability of the future generation through the exploitation of the current elements of survival such as natural resources and destruction of the ecosystem. Developed countries have been spotted to take advantage of both developing countries and underdeveloped countries because they own personnel and equipment that can be useful in the extraction of natural resources. Aspects of humanity understand the need for protecting the environment and natural resources through different environmental laws that aid in governing efficacy in human nature coexistence. Moreover, the efficacy of good governance across developing countries depends on the structure of the governing body and the economic resources available to withstand the population growth within the region. Also, developing countries are on the verge of declining control and management of efficient environment policies that align with the management of the current levels of climatic changes. Some of the concerns covered under environmental laws incorporate different types of pollution, the sustainability of resources such as forestry, minerals, and water, and certain principles and policies related to environmental concerns. Poverty encroachment in developing countries has been steered by the encroachment of land degradation, pollution, and other environmental crisis. In many regions across developing countries, there exists a pressure exerted on the exploitation of natural resources arising from the increased population and meeting the global demand of the ever-growing market. With the continued climatic changes across the world, developing countries are experiencing strains to maintain the ever rising heat on implementation of environmental laws and natural resources policies. The research discusses the effects of climatic changes on the existing environmental laws and impact on natural resource policies.